Primary percutaneous coronary intervention in octogenarians. (1st November 2016) - Ricci, Beatrice; Manfrini, Olivia; Cenko, Edina; Vasiljevic, Zorana; Dorobantu, Maria; Kedev, Sasko; Davidovic, Goran; Zdravkovic, Marija; Gustiene, Olivija; Knežević, Božidarka; Miličić, Davor; Badimon, Lina; et al.
Abstract: Background: Limited data are available on the outcome of primary percutaneous coronary intervention (PCI) in octogenarian patients, as the elderly are under-represented in randomized trials. This study aims to provide insights on clinical characteristics, management and outcome of the elderly and very elderly presenting with STEMI. Methods: 2225 STEMI patients ≥ 70 years old (mean age 76.8 ± 5.1 years and 53.8% men) were admitted into the network of the ISACS-TC registry. Of these patients, 72.8% were ≥ 70 to 79 years old (elderly) and 27.2% were ≥ 80 years old (very-elderly). The primary end-point was 30-day mortality. Results: Thirty-day mortality rates were 13.4% in the elderly and 23.9% in the very-elderly. Primary PCI decreased the unadjusted risk of death both in the elderly (OR: 0.32, 95% CI: 0.24–0.43) and very-elderly patients (OR: 0.45, 95% CI 0.30–0.68), without significant difference between groups. In the very-elderly hypertension and Killip class ≥ 2 were the only independent factors associated with mortality; whereas in the elderly female gender, prior stroke, chronic kidney disease and Killip class ≥ 2 were all factors independently associated with mortality. Factors associated with the lack of use of reperfusion were female gender and atypical chest pain in the very-elderly and in the elderly; in the elderly, however, there were some more factors, namely: history of diabetes, current smoking, prior stroke, Killip class ≥ 2 and history chronic kidney disease. Conclusions: Age is relevant in the prognosis of STEMI, but its importance should not be considered secondary to other major clinical factors. Primary PCI appears to have beneficial effects in the octogenarian STEMI patients. Highlights: Octogenarians are a growing segment of the population with acute coronary syndrome. Old subjects are commonly considered as a unique cohort. Specific evaluation of differences in older STEMI subgroups is warranted. Different factors may influence clinicians' decision on the elderly and very elderly Primary PCI appears to have beneficial effects even in patients ≥ 80 years.